2014
DOI: 10.1016/j.ijhcs.2013.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Using the health belief model to explore users' perceptions of ‘being safe and secure’ in the world of technology mediated financial transactions

Abstract: Fraudulent transactions occurring via the Internet or Automatic Teller Machines (ATMs) present a considerable problem for financial institutions and consumers alike. Whilst a number of technological improvements have helped reduce the likelihood of security breaches, users themselves have an integral role to play in reducing technology mediated fraud. This paper focuses on the role of the user, specifically capturing information about their perceptions and behaviour when using technology to complete financial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 68 publications
1
26
0
Order By: Relevance
“…However, all these e-platforms are prone to attacks with unintended consequences on customers and distrust in the e-payment systems. Davinson and Sillence (2014) aver that fraudulent transactions via the internet or ATMs present a considerable problem for financial institutions and customers. This is because millions of transactions are mediated by technology usually deployed within a cashless ecosystem like Nigeria.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…However, all these e-platforms are prone to attacks with unintended consequences on customers and distrust in the e-payment systems. Davinson and Sillence (2014) aver that fraudulent transactions via the internet or ATMs present a considerable problem for financial institutions and customers. This is because millions of transactions are mediated by technology usually deployed within a cashless ecosystem like Nigeria.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Some examples of such predictive, preventive, and comprehensive behaviours could be (i) identifying online security behaviour such as password management and obtaining security training (Stanton, Mastrangelo, Stam, & Jolton, 2004); (ii) proposing a conceptual model of user security behaviour based on risk perception (Aytes & Conolly, 2003); (iii) attitudes towards online gambling and player protection (Wijesingha, Leatherdale, Turner, & Elton-Marshall, 2017); (iv) examining online privacy concern in Facebook users (Saeri, Ogilvie, La Macchia, Smith, & Louis, 2014) and teens' online privacy protection and subsequent online information disclosure on social network sites (Hongliang Chen et al, 2016); understanding individual email protection (Herath et al, 2014). The HBM has also been utilized to explore users' perceptions of being safe and secure online (Davinson & Sillence, 2014), and the impact of online and offline friendship networks on adolescent smoking and alcohol use (Huang et al, 2014). Youn (2005), tested the threat appraisal component of PMT to examine the context of online safety and found that higher levels of risk perception motivate teenagers to protect themselves from online privacy threats.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…Goal‐pursuit research shows that activating a goal increases not only commitment but also implementation‐intentions toward reaching said goal (Carver & Scheier, ; Covington, ; Gollwitzer, ; Van Osselaer & Janiszewski, ). Hence, since priming prevention focus increases concerns for financial safety and security (Davinson & Sillence, ; Spiegel, Grant‐Pillow, & Higgins, ; Van Noort, Kerkhof, & Fennis, ), it is logical to expect greater commitment toward ensuring a better financial situation. In our context of intertemporal choice, this means a lesser sensitivity to the pain associated with delaying a reward.…”
Section: Conceptual Developmentmentioning
confidence: 99%